Conservation of Peary caribou based on a recalculation of the 1961 aerial survey on the Queen Elizabeth Islands, Arctic Canada - Miller, Frank L.; Barry, Samuel J.; Calvert, Wendy A. (Rangifer, 2005)
The estimate of 25 845 Peary caribou (Rangifer tarandus pearyi) on the Queen Elizabeth Islands (QEI) in the Canadian High Arctic in summer 1961 is the only nearly range-wide 'benchmark' for the past number of caribou. No variances or confidence intervals were calculated for this estimate and no estimates were calculated for Peary caribou on the three major islands of Ellesmere, Devon, and Axel Heiberg. We reexamined the 1961 raw data by grouping the QEI into five island-complexes ('eco-units') and calculating, for each unit, the estimated number of caribou and the standard error, and the 95% confidence interval of the estimate, using a 'bootstrap' technique with 100 000 replications. Our goal was to provide an ecological basis for evaluating subsequent changes in numbers rather than relying on single-island evaluations. Our bootstrap reanalysis produced an estimate of 28 288 ± 2205 SE with a 95% CI of 20 436—37 031 Peary caribou on the QEI in summer 1961. Substantial differences in density were apparent among the five eco-units, with about a 50-fold difference from 0.01 caribou • km-2 in the Eastern eco-unit to 0.5 caribou • km-2 in the Northwestern eco-unit. The 1961 findings, with our subsequent reexamination, are crucial to any evaluation of trends for the number of Peary caribou on the QEI and the relative importance of individual eco-units for these animals. These findings also allow a more accurate evaluation of the magnitude of the subsequent decline of Peary caribou on the QEI during the last four decades and may help predict future potential levels for caribou in each of the five eco-units.
Keywords: aerial survey; Canada; caribou; Canadian High Arctic Islands; conservation; distribution; management; numbers; Rangifer tarandus pearyi